2002
DOI: 10.1016/s0885-3924(02)00383-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Once-Daily Morphine Formulation in Chronic, Moderate-to-Severe Osteoarthritis Pain

Abstract: A randomized, 4-week, double-blind trial followed by an open-label extension trial assessed the efficacy and safety of a once-daily, extended-release morphine formulation (Avinza (previously referred to as Morphelan)) in 295 patients with chronic, moderate-to-severe osteoarthritis pain who had failed to obtain adequate pain relief with NSAIDs and acetaminophen. Participants received one of four treatments: Avinza 30 mg once daily (QAM or QPM), MS Contin(R) 15 mg twice daily, or placebo twice daily. Patients (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(14 citation statements)
references
References 27 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…The overall rates appear toward the higher range of discontinuation rates of 38%–63% observed in other studies using opioid therapy over a 2–6-month period for management of chronic, moderate-to-severe pain,16,23,2528 possibly due to the amount and types of monitoring required of patients. The discontinuation rates due to adverse events and treatment failure were similar to those reported in other studies 16,23,2528. Unlike other studies, this study required that patients identified at high risk for opioid abuse be withdrawn.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The overall rates appear toward the higher range of discontinuation rates of 38%–63% observed in other studies using opioid therapy over a 2–6-month period for management of chronic, moderate-to-severe pain,16,23,2528 possibly due to the amount and types of monitoring required of patients. The discontinuation rates due to adverse events and treatment failure were similar to those reported in other studies 16,23,2528. Unlike other studies, this study required that patients identified at high risk for opioid abuse be withdrawn.…”
Section: Discussionmentioning
confidence: 69%
“…The current multicenter, uncontrolled, open-label study,14 conducted in the primary care setting among a broad geographically distributed population, evaluated the effectiveness and tolerability of morphine sulfate extended-release capsules (Avinza ® , King Pharmaceuticals Inc, Bristol, TN, acquired by Pfizer Inc in March 2011) in patients with chronic, moderate-to-severe pain 15. Effectiveness, an evaluation of treatment under real-world conditions,16,17 was based on pain and functional assessments. This study was also designed to assess risk of opioid misuse and abuse, and the utility of a universal precautions approach in the primary care setting.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of morphine in this OA model is in accordance with previous studies [11,15,27] where similar doses of morphine had anti-nociceptive effects demonstrated by WB changes. In a human study, morphine was efficacious in reducing pain in patients with moderate-to-severe OA [28]. The demonstrated antinociceptive effect of morphine provides support for the endpoint of unrestricted WB as a reliable method to evaluate MIA-induced pain.…”
Section: Morphinementioning
confidence: 83%
“…The characteristics of each included study are summarized in the Supplementary material. 149–1214–16182327303537–485458616567707275 The frequency of the different types of study design (for the purposes of analysis), control group (controlled studies only), and opioid type along with the quality of the included articles in terms of Jadad score is given for the ‘rescue’ and ‘no rescue’ studies and overall in Table 1. The maximum time of treatment was 2 yr.…”
Section: Resultsmentioning
confidence: 99%